Teaching of Non- Linguistic Disciplines (NLD) in Secondary school in Morocco: Reference, organizational, pedagogical and procedural requirements towards improving learning - EL GUAMRI, Youssef; AMAHMID, Omar; RAKIBI, Youness; FAKIHANI, Abdelhalim; YAZIDI, Mohamed; RAZOKI, Bouchra; RASSOU, Khaidija KAID; OUIZAT , Saadia; SERRAR, Ouafae (Journal of Curriculum and Teaching Methodology, 2024)
The study evaluated the teaching of scientific subjects in foreign languages at the secondary school level in Morocco, using a descriptive analytical approach. It analyzed ministerial correspondence, memorandums, and national and international reports, focusing on reference, organizational, and pedagogical requirements to improve learning. The study comprised four sections: the first addressed the Moroccan International Baccalaureate in terms of objectives, target groups, and admission criteria; the second examined the legislative and organizational framework; the third discussed issues related to teachers, learners, and curricula; and the fourth outlined assessment procedures. Key findings included: (1) linking linguistic engineering with comprehensive curriculum reviews, (2) preparing educators with multilingual competencies, (3) developing teaching resources, and (4) reforming assessment systems. The study recommended developing curricula aligned with global educational trends, enhancing teacher training programs to improve foreign language proficiency, and conducting further studies on the topic.